Influence of annealing on the properties of (Cd, Mn)Te crystals. Issue 9 (14th May 2014) - Witkowska‐Baran, M.; Kochanowska, D. M.; Mycielski, A.; Jakieła, R.; Wittlin, A.; Knoff, W.; Suchocki, A.; Nowakowski, P.; Korona, K.
Abstract Semi‐insulating (Cd, Mn)Te crystals are believed to be suitable to successfully replace the commonly used (Cd, Zn)Te and CdTe crystals as a material for manufacturing large‐area X‐ and γ‐ray detectors. The purpose of the studies was to elaborate the technology of the (Cd, Mn)Te crystal plates with high resistivity, uniform in the whole volume of the plate. The article presents a method of annealing of the monocrystalline (Cd, Mn)Te crystal plates, giving the desired, repeatable results. The semi‐insulating (Cd, Mn)Te crystals, doped (for compensation) mainly by vanadium, but sometimes by Cl, In, or Cl and V, were grown by the Bridgman method, and the monocrystalline plates were cut. Subsequently the plates were annealed in Cd vapour. The resistivity of the plates was around 109 Ωcm, and the μτ‐product was about 10‐4 ‐10‐3 cm2/V. Mapping of the resistivity was performed on both the as‐grown crystals and the annealed crystal plates. The resistivity of the as‐grown crystals was in the range of 105‐106 Ωcm and inhomogeneous. After annealing the resistivity increased up to 109 Ωcm and better homogeneity could be seen. Annealing in the saturated Cd vapour influenced tellurium inclusions/precipitates. It was studied by IR transmission microscopy. For the as‐grown samples the density of Te inclusions (>1 µm) was ≈ 4×105 cm‐3, but for the annealed samples it was ≈ 104 cm‐3. The low‐temperature photoluminescence (PL) measurements indicated significantly lowered concentrations of acceptors after annealing. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)